Functional characterization and transient expression manipulation of a new sesquiterpene synthase involved in beta-caryophyllene accumulation in Ocimum - Jayaramaiah, Ramesha H.; Anand, Atul; Beedkar, Supriya D.; Dholakia, Shushan B.; Punekar, Sachin A.; Kalunke, Raviraj M.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochemical And Biophysical Research Communications, 2016)
The genus Ocimum has a unique blend of diverse secondary metabolites, with major proportion of terpenoids including mono- and sesquiterpenes. Although, beta-Caryophyllene, bicyclic sesquiterpene, is one of the major terpene found in Ocimum species and known to possess several biological activities, not much is known about its biosynthesis in Ocimum. Here, we describe isolation and characterization of beta-caryophyllene synthase gene from Ocimum kilimandscharicum Gurke (OkBCS- GenBank accession no. KP226502). The open reading frame of 1629 bp encoded a protein of 542 amino acids with molecular mass of 63.6 kDa and pl value of 5.66. The deduced amino acid sequence revealed 50-70% similarity with known sesquiterpene synthases from angiosperms. Recombinant OkBCS converted farnesyl diphosphate to beta-caryophyllene as a major product (94%) and 6% alpha-humulene. Expression variation of OkBCS well corroborated with beta-caryophyllene levels in different tissues from five Ocimum species. OkBCS transcript revealed higher expression in leaves and flowers. Further, agro-infiltration based transient expression manipulation with OkBCS over-expression and silencing confirmed its role in beta-caryophyllene biosynthesis. These findings may potentially be further utilized to improve plant defense against insect pests. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: beta-Caryophyllene; Natural product biosynthesis; Ocimum; Terpene synthase; Transient expression

Terpene profiling, transcriptome analysis and characterization of cis–terpineol synthase from Ocimum - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Dholakia, Bhushan B.; Lavhale, Santosh G.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Physiology and Molecular Biology of Plants, 2019)
Ocimum species produces a varied mix of different metabolites that imparts immense medicinal properties. To explore this chemo-diversity, we initially carried out metabolite profiling of different tissues of five Ocimum species and identified the major terpenes. This analysis broadly classified these five Ocimum species into two distinct chemotypes namely, phenylpropanoid-rich and terpene-rich. In particular, -caryophyllene, myrcene, limonene, camphor, borneol and selinene were major terpenes present in these Ocimum species. Subsequently, transcriptomic analysis of pooled RNA samples from different tissues of Ocimum gratissimum, O. tenuiflorum and O. kilimandscharicum identified 38 unique transcripts of terpene synthase (TPS) gene family. Full-length gene cloning, followed by sequencing and phylogenetic analysis of three TPS transcripts were carried out along with their expression in various tissues. Terpenoid metabolite and expression profiling of candidate TPS genes in various tissues of Ocimum species revealed spatial variances. Further, putative TPS contig 19414 (TPS1) was selected to corroborate its role in terpene biosynthesis. Agrobacterium-mediated transient over-expression assay of TPS1 in the leaves of O. kilimandscharicum and subsequent metabolic and gene expression analyses indicated it as a cis–terpineol synthase. Overall, present study provided deeper understanding of terpene diversity in Ocimum species and might help in the enhancement of their terpene content through advanced biotechnological approaches.
Keywords: Agro-infiltration assay; Metabolite profiling; Ocimum; Terpene synthase; Terpenes; Transcriptome

Generation of novelties in the genus Ocimum as a result of natural hybridization: a morphological, genetical and chemical appraisal - Gurav, Tanuja P.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Dholakia, Bhushan B.; Giri, Ashok P. (Industrial Crops and Products, 2020)
The genus Ocimum is a boutique of a diverse set of specialized metabolites such as terpenoids and phenylpropanoids. Each Ocimum species and its cultivars represent a characteristic chemical profile. The present study explored the two interspecific Ocimum hybrids originating through a serendipitous natural cross between O. kilimandscharicum and O. basilicum. These two novel Ocimum hybrids exhibited intermediate morphological features of two parental species. Inter simple sequence repeats (ISSR) analysis and DNA barcoding with the plastid non-coding trnH-psbA intergenic spacer region reaffirmed unambiguous parental identification and differentiation of these natural hybrids from other available Ocimum species. Consequently, gas chromatographymass spectrometry-based metabolite profiling of two hybrids identified them as specific chemotypes with the presence of a unique blend of specialized metabolites from the parental species, which are either rich in terpenes or phenylpropanoids. Additionally, expression analysis of key genes from terpenoid and phenylpropanoid pathways corroborated with differential metabolite accumulation. Thus, these two Ocimum hybrids represented the novel chemotypes, which could be useful in commercial cultivation to produce novel essential oil and bioactive constituents. Further, the resulting metabolite diversity could have potential industrial applications in the areas of healthcare, bioremediation, and crop protection.
Keywords: Chemotype; DNA barcoding; Inter Simple Sequence Repeats; Interspecific hybrid; O. basilicum; O. kilimandscharicum; Ocimum

Glance at the chemodiversity of Ocimum species: Trends, implications, and strategies for the quality and yield improvement of essential oil - Gurav, Tanuja P.; Dholakia, Bhushan B.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Ocimum species represent commercially important medicinal and aromatic plants. The essential oil biosynthesized by Ocimum species is enriched with specialized metabolites specifically, terpenoids and phenylpropanoids. Interestingly, various Ocimum species are known to exhibit diverse chemical profiles, and this chemical diversity has been at the center of many studies to identify commercially important chemotypes. Here, we present various chemotypes from the Ocimum species and emphasize trends, implications, and strategies for the quality and yield improvement of essential oil. Globally, many Ocimum species have been analyzed for their essential oil composition in over 50 countries. Asia represents the highest number of chemotypes, followed by Africa, South America, and Europe. Ocimum basilicum L. has been the most widespread and well-studied species, followed by O. gratissimum L., O. tenuiflorum L., O. canum Sims, O. americanum and O. kilimandscharicum Gurke. Moreover, various molecular reasons, benefits, adverse health effects and mechanisms behind this vast chemodiversity have been discussed. Different strategies of plant breeding, metabolic engineering, transgenic, and tissue-culture, along with anatomical modifications, are surveyed to enhance specific chemotypic profiles and essential oil yield in numerous Ocimum species. Consequently, chemical characterization of the essential oil obtained from Ocimum species has become indispensable for its proper utilization. The present chemodiversity knowledge from Ocimum species will help to exploit various applications in the industrial, agriculture, biopharmaceutical, and food sectors.
Keywords: Chemodiversity; Chemotype; Essential oil; Metabolic engineering; Ocimum; Specialized metabolites